Climate variations in the Northern Hemisphere based on the use of an atmosphere-ocean IPCC model - Volodin, E. M.; Diansky, N. A.; Lanucara, P.; Purini, R.; Transerici, C. (Societa italiana di fisica, 2008)
Forced and natural variability of modelled and observed Atlantic Ocean temperature and Atlantic Meridional Overturning Circulation (AMOC) is studied. In the observations and in a forced climate model run, we find increasing temperature at 1000m in the Atlantic (20N). SVD analysis shows that, for both model data and observations, a high index of North Atlantic Oscillation (NAO) corresponds to negative temperature anomaly at 1000m to the north of 55N, although geographical details of temperature anomaly distribution are different for the model and observations. Particular attention has been paid to the influence of the fresh water flux due to the present global warning on the slowing down of the AMOC. It is shown that fresh water flux change is only a secondary cause of reduced AMOC in global warming conditions, while heat flux change is probably the main reason. Finally, it is shown that internal model AMOC variability is positively correlated with the near-surface air temperature in Atlantic-European Arctic sector on a 10-year time scale.